Exposure to human-associated fecal indicators and self-reported illness among swimmers at recreational beaches: a cohort study - Melanie D. Napier; Richard Haugland; Charles Poole; Alfred P. Dufour; Jill R. Stewart; David J. Weber; Manju Varma; Jennifer S. Lavender; Timothy J. Wade (BMC, 2017)
Abstract Background Fecal indicator bacteria used to assess illness risks in recreational waters (e.g., Escherichia coli, Enterococci) cannot discriminate among pollution sources. To address this limitation, human-associated Bacteroides markers have been proposed, but the risk of illness associated with the presence of these markers in recreational waters is unclear. Our objective was to estimate associations between human-associated Bacteroides markers in water and self-reported illness among swimmers at 6 U.S. beaches spanning 2003-2007. Methods We used data from a prospectively-enrolled cohort of 12,060 swimmers surveyed about beach activities and water exposure on the day of their beach visit. Ten to twelve days later, participants reported gastroinestinal, diarrheal, and respiratory illnesses experienced since the visit. Daily water samples were analyzed for the presence of human-associated Bacteroides genetic markers: HF183, BsteriF1, BuniF2, HumM2. We used model-based standardization to estimate risk differences (RD) and 95% confidence intervals (CI). We assessed whether the presence of Bacteroides markers were modifiers of the association between general Enterococcus and illness among swimmers using interaction contrast. Results Overall we observed inconsistent associations between the presence of Bacteroides markers and illness. There was a pattern of increased risks of gastrointestinal (RD = 1.9%; 95% CI: 0.1%, 3.7%), diarrheal (RD = 1.3%; 95% CI: -0.2%, 2.7%), and respiratory illnesses (RD = 1.1%; 95% CI: -0.2%, 2.5%) associated with BsteriF1. There was no evidence that Bacteroides markers acted as modifiers of Enterococcus and illness. Patterns were similar when stratified by water matrix. Conclusions Quantitative measures of fecal pollution using Bacteroides, rather than presence-absence indicators, may be necessary to accurately assess human risk specific to the presence of human fecal pollution.